Selection of Suitable Drilling Parameters for obtaining high Rate of Penetration in Majnoon Oilfield - M. Majeed, Majid; A. Alhaleem, Ayad (Iraqi Journal of Chemical and Petroleum Engineering, 2019)
Several directional wells have been drilled in Majnoon oilfield at wide variation in drilling time due to different drilling parameters applied for each well. This technical paper shows the importance of proper selection of the bit, Mud type, applied weight on Bit (WOB), Revolution per minute (RPM), and flow rate based on the previous wells drilled. Utilizing the data during drilling each section for directional wells that’s significantly could improve drilling efficiency presented at a high rate of penetration (ROP). Based on the extensive study of three directional wells of 35 degree inclination (MJ-51, MJ-52, and MJ-54) found that the applied drilling parameters for MJ-54 and the bit type within associated drilling parameters to drill 36", 24", 16" and 12 1/4" hole sections is the best, although the drilling parameters in 8 1/2" hole section for MJ-51 and selected bit type are the best for future wells.